2020
DOI: 10.1111/apa.15443
|View full text |Cite
|
Sign up to set email alerts
|

Missing during COVID‐19 lockdown: Children with onset of type 1 diabetes

Abstract: The redistribution of healthcare resources for coronavirus 2019 (COVID-19) pandemic has resulted in unintentional neglect of essential non-COVID-19 care. 1 In low-and lower-middle-income countries, the already overstretched healthcare systems have crumbled under the COVID-19 pressure. 1 In India, the first COVID-19 case was detected on January 30, and a nationwide total lockdown was announced from March 25 until May 3, 2020, followed by a partial lockdown. The hard-line lockdown restrictions and fear of exposu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 7 publications
4
46
0
5
Order By: Relevance
“…Furthermore, there is ample international evidence that point to adverse consequences due to care avoidance. For example, although Dayal et al reported a 75% reduction in the number of new diabetes cases during lockdown, the authors described three patients who have been diagnosed during lockdown and suffered from severe diabetic keto-acidosis, in which parents declared they delayed seeking care due to COVID-19 circumstances [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is ample international evidence that point to adverse consequences due to care avoidance. For example, although Dayal et al reported a 75% reduction in the number of new diabetes cases during lockdown, the authors described three patients who have been diagnosed during lockdown and suffered from severe diabetic keto-acidosis, in which parents declared they delayed seeking care due to COVID-19 circumstances [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has revealed that healthcare professionals have been observing an increased incidence of diabetic ketoacidosis in youth [1] , [2] , [3] , possibly attributed to parents avoiding hospital visits due to the concern of potential infection with COVID-19 [3] . Similarly, for individuals living with diabetes, the COVID-19 pandemic is correlated with increased variability in glycemic control and a reduction in physical activity [4] , which may be a result of stay-at-home recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian Federation of Independent Business recently estimated that 12% of small and medium-sized BC businesses are at risk of closure (Gaudreault, 2020; McCusker and Tindale, 2020), but estimates of the effect of these possible closures on provincial GDP is not yet known. Second, with hospitals stretched to accommodate COVID-19 patients, and with fear of contracting COVID-19 limiting movement, treatment of non-COVID illnesses can be severely delayed (Dayal et al, 2020; Lazzerini et al, 2020). Thus there will be excess deaths from other causes, and costs associated with suffering due to untreated conditions (Dayal et al, 2020; Solis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Second, with hospitals stretched to accommodate COVID-19 patients, and with fear of contracting COVID-19 limiting movement, treatment of non-COVID illnesses can be severely delayed (Dayal et al, 2020; Lazzerini et al, 2020). Thus there will be excess deaths from other causes, and costs associated with suffering due to untreated conditions (Dayal et al, 2020; Solis et al, 2020). Finally, mental health, in general, is known to suffer during community disasters (Lowe et al, 2019; North and Pfefferbaum, 2013), including pandemics.…”
Section: Discussionmentioning
confidence: 99%